2021
DOI: 10.1186/s40834-020-00145-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of immediate postpartum insertion of TCu380A on the quantity and duration of lochia discharges in Tanzania

Abstract: Background The insertion of Intrauterine Contraceptive Device (PPIUD) for the purpose of contraception immediately after delivery is becoming popular in countries where the use of IUD for contraception has been extremely low. Since 2015, Tanzania implemented the initiative by the International Federation of Gynecology and Obstetrics (FIGO) to institutionalize PPIUD. As a result of capacity building and information delivery under the initiative, there have been increased uptake of the method. Wo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This lochia-rich alkaline vaginal milieu during postpartum is a haven for the proliferation of BVAB. Discharge rates, volume, and cessation of lochia during post-delivery differs between subjects, but typically lasts about 6–8 weeks ( 97 , 98 ) or more ( 99 ). This raises an important question of what period of time will any lochia driven BVAB vagitype revert to a Lactobacillus state after lochia cessation.…”
Section: Methodsmentioning
confidence: 99%
“…This lochia-rich alkaline vaginal milieu during postpartum is a haven for the proliferation of BVAB. Discharge rates, volume, and cessation of lochia during post-delivery differs between subjects, but typically lasts about 6–8 weeks ( 97 , 98 ) or more ( 99 ). This raises an important question of what period of time will any lochia driven BVAB vagitype revert to a Lactobacillus state after lochia cessation.…”
Section: Methodsmentioning
confidence: 99%
“…[21][22][23] Furthermore, there are no studies looking at the impact of PPIUD use on the risk of developing anemia within the postpartum population. One study 24 has reported increased lochia following PPIUD when comparing to non-PPIUD users in Tanzania, but a link with anemia was not sought. Given the national intention to expand access to postpartum contraception and increase uptake of LARCs such as the copper IUD, this study aimed to increase the evidence base on the clinical implications of PPIUD use on hemoglobin levels as a proxy measure of anemia.…”
mentioning
confidence: 99%